Investigation of Magnetically Insulated Diode for Intense Pulsed Ion Beam Generation for Materials Research; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Xiao Yu; Shijian Zhang; Stepanov A. V. Andrey Vladimirovich; Shamanin V. I. Vitaly Igorevich; Haowen Zhong; Xiaojun Cui; Guoying Liang; Mofei Xu; Nan Zhang; Shicheng Kuang; Jianhui Ren; Sha Yan; et al. (New Accelerator Systems and Tools for Materials Research. Poster Session, 2019)
Заглавие с экрана